Reformasi Hukum Keluarga Islam Berbasis Maqasid Al-Syari’ah : Upaya Perlindungan terhadap Anak di Bawah Umur - Andi Silva Quadsajul; Aura Lika Cahyani Andi Sufarid; Andi Maharani Erwin; Kuniati Kuniati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This research is motivated by the phenomenon of marriage of minors (al-Zawaj al-Mubakkir) which socially causes various negative impacts (mafsadah) such as reproductive health disorders, school dropout, and psychological immaturity, although in classical Fiqh discourse this practice is found to be justified and allowed by some scholars. Faced with the contradiction between flexible classical provisions and adverse contemporary realities, this study aims to analyze the urgency of reforming Islamic Family Law, especially regarding the age limit of marriage, based on Maqasid al-Sharia. The methodology used is a normative-contextual analysis by applying the maqāṣid framework, especially the principles of life protection (hifz al-nafs), reason (hifz al-’aql), and heredity (hifz al-nasl) to evaluate the provisions of the law. The results of the study showed that the Maqāṣid al-Shari’ah supported a shift in the standard of maturity for marriage from merely a biological sign (baligh) to psychic maturity and the ability to bear responsibility (Rushd). This reform, which is in line with law No. 16 of 2019, serves as a strategic instrument to guarantee the protection of children and encourage the transformation of family law into a more substantial-humanistic one.